Spatio-Temporal Pattern of Dinoflagellates Along the Tropical Eastern Pacific Coast (Ecuador) - Torres, Gladys; Carnicer, Olga; Canepa, Antonio; De La Fuente, Patricia; Recalde, Sonia; Narea, Richard; Pinto, Edwin; Borbor-Córdova, Mercy J. (Frontiers in Marine Science, 2019)
Among marine phytoplankton, dinoflagellates are a key component in marine ecosystems as primary producers. Some species synthesize toxins, associated with human seafood poisoning and mortality in marine organisms. Thus, there is a large necessity to understand the role of environmental variables in dinoflagellates spatial-temporal patterns in response to future climate scenarios. In that sense, a monthly four-year (2013-2017) monitoring was taken to evaluate dinoflagellates abundances and physical-chemical parameters in the water column at different depths. Sampling sites were established at 10 miles in four locations within the Ecuadorian coast. A total of 97 taxa were identified, corresponding to 7 orders, 19 families, 28 genera. Eight potentially harmful genera were registered but no massive blooms were detected. The most frequent dinoflagellates were Gymnodinium sp. and Gyrodinium sp. Environmental variables showed different mixing layer thickness and a conspicuous and deepening thermocline / oxycline / halocline and nutricline depending on annual and seasonal oceanographic fluctuations. This study confirms that seasonal and spatial distribution of the environmental variables are linked to the main current systems on the Eastern Tropical Pacific, thus the warm Panama current lead to a less dinoflagellates abundance in the north of Ecuador (Esmeraldas), while the Equatorial Upwelling and the cold nutrient-rich Humboldt Current influence dinoflagellates abundance at the central (Manta, La Libertad) and South of Ecuador (Puerto Bolivar) respectively. Inter-annual variability of dinoflagellates abundance is associated with ENSO and upwelling conditions. Climate change scenarios predict an increase in water surface temperature and extreme events frequency in tropical areas, so it is crucial to involve policy-makers and stakeholders in the implementation of future laws involving long-term monitoring and sanitary programs, not covered at present.